Video Production: Getting Started - Ricky Telg (EDIS)
Today, just about anyone can post videos on the Web so that friends and family can see them, capture news events and distribute them online to television stations or networks that have websites, or shoot video “in the field” and bring the “field” back to the classroom. This 2-page fact sheet has information for novice video producers about developing video productions. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.